COVID‐19 impact, sustainability performance and firm value: international evidence. (6th May 2021) - Bose, Sudipta; Shams, Syed; Ali, Muhammad Jahangir; Mihret, Dessalegn
Abstract: We examine the impact of COVID‐19 on changes in firm value, and the moderating role of firm‐level sustainability performance on this relationship. We find that firms domiciled in countries where the COVID‐19 impact is more devastating experienced greater decline in firm value. The negative impact of COVID‐19 on firm value is less pronounced for firms with better sustainability performance. Firms domiciled in countries with higher levels of environmental‐ and stakeholder‐value‐oriented culture experienced less decline in firm value from the impact of COVID‐19. Findings suggest a firm's stakeholder‐value orientation contributes to preserving a firm's value when general stakeholder value declines.